(untitled) (Conference Zone, 2022)
The goal of an experiential language learning approach is to provide learners with “concrete experiences through which they ‘discover’ language principles even if subconsciously by trial and error, by processing feedback, by building hypotheses about language, and by revising those assumptions in order to become fluent”